Safe management of bodies of deceased person with suspected or confirmed COVID-19 - Bhattarai, Aabishkar; Karki, Bijaya (Journal of Advances in Internal Medicine, 2020)
COVID-19 is a respiratory illness caused by COVID-19 the coronavirus that predominantly affects the lungs. Because of limited data and research studies, the transmission of the virus from dead bodies with COVID-19 has not been verified. However, to stay on a safe side, the safety and well-being of everyone who handles the corpses should be prioritized. All the personnel who interact with the dead bodies (Health Care Workers, Ambulance drivers, Mortuary staffs or Burial teams) should apply the standard precautionary measures including Personal Protective Equipment (gown, gloves, and face protection-face mask and face shield if risks of splashes from body fluids are high). Safety precautions should be taken by the forensic personnel involved in the autopsies of the people who died from COVID-19, as the lungs and other organs can still contain a live virus.